Sleep impact on obesity – literature review - Kacper Buczek; Klaudia Kulig; Maksymilian Wiśniowski; Dominik Stanibuła; Patrycja Zwierzchlewska; Aneta Redner; Jakub Rybowski; Michal Popiel; Julia Głowacz; Kamil Dziekoński (Quality in Sport)
Purpose: The aim of this literature review is to analyze existing studies on the relationship between sleep and obesity, with a focus on how sleep quality, duration, and circadian rhythm disruptions influence obesity development. It also identifies biological mechanisms, such as changes in appetite-regulating hormones, and evaluates the effectiveness of sleep-related interventions in obesity prevention and treatment.